Comparison of Two Extubation Techniques in Critically Ill Adult Subjects: The ExtubAR Randomized Clinical Trial - Andreu, Mauro; Bertozzi, Matías; Bezzi, Marco; Borello, Silvina; Castro, Daniela; Giorgio, Victoria Di; Aguirre, Mariana (Respiratory care, 2022)
Two orotracheal extubation techniques are described in the literature: the traditional technique and the positive-pressure technique. Although prior studies reported better clinical outcomes with the positive-pressure extubation technique, its superiority has not been extensively studied yet. This study was to determine whether the positive-pressure orotracheal extubation technique, compared with the traditional orotracheal extubation technique, reduces the incidence of major postextubation complications (up to 60 min) in critically ill adult subjects. This was a multi-center randomized clinical trial. Subjects age > 18 y, requiring invasive mechanical ventilation through an endotracheal tube, who met the orotracheal extubation criteria were included and randomized to traditional extubation group (removing the endotracheal tube by applying continuous endotracheal suctioning during the entire procedure) or positive-pressure group (application of pressure support mode at 15/10 cm H O during cuff deflation and extubation). The primary measure was postextubation major complications, defined as the clinical evidence of at least one of the following: desaturation, upper-airway obstruction, or vomiting. A total of 725 subjects was randomly assigned to the traditional extubation group ( = 358) and positive-pressure group ( = 367). Seventeen subjects were eliminated and not included in the per-protocol analysis. Of 708 subjects, 185 (26.1%) developed at least one major complication. The incidence was 27.8% (96/345) in the traditional group compared with 24.5% (89/363) in the positive-pressure group. No statistically significant differences were observed between the 2 groups (absolute risk 3% [95 CI -3 to 10]; relative risk, 0.88 [95 CI 0.69-1.13], = .32). Despite the trend toward the positive-pressure group, no statistically significant differences were observed. Our findings agree with the literature in that positive-pressure extubation is a safe procedure; therefore, both techniques may be used during extubation in critically ill adult patients.